Pregnancy vaccination guide - Monika Zasztowt-Sternicka; Aneta Nitsch-Osuch (Family Medicine & Primary Care Review, 2024)
Vaccinations are the most effective and economically beneficial form of preventing dangerous infectious diseases. Healthcare professionals should strive for the highest possible immunisation rate in the population, especially among patients from risk groups, which include pregnant women. The vaccination coverage among pregnant Polish women is still unsatisfactory. A consensus on vaccination of pregnant women has recently been achieved by the greatest scientific authorities: global organisations and scientific societies recommend all pregnant women to be vaccinated against pertussis, influenza and COVID-19. Vaccination during pregnancy leads to the production of post-vaccination antibodies that migrate transplacentally to the foetus, providing protection to infants in their first months of life. The inactivated influenza vaccine is safe and effective when given at any stage of pregnancy. Vaccination against pertussis should take place between week 27 and 36 of pregnancy. The COVID-19 vaccine can be administered simultaneously with other vaccines or with a 14-day interval. The American Congress of Obstetricians and Gynecologists (ACOG) recommends vaccination of pregnant women with mRNA COVID-19 vaccines at any stage of pregnancy. As a general rule, pregnant women should not be vaccinated with live, attenuated viruses or bacterial vaccines. Vaccines contra-indicated for pregnant individuals, such as the vaccine against measles, mumps, rubella and varicella, as well as HPV, can be administered after delivery and during the breastfeeding period. Vaccination of pregnant women against rabies or tetanus is necessary for post-exposure prophylaxis.